Evaluation of strategies to improve efficiency in swine production and minimize pathogen transmission through feed - Gebhardt, Jordan Thomas (Kansas State University, 2020)
Efficient use of resources is an important goal of modern agriculture. Several approaches to maximize resource utilization in swine production were evaluated including dietary approaches and interventions within the feed manufacturing process to optimize animal health. A total of 7,842 pigs were used over a total of 10 experiments structured in 6 chapters. Chapter 1 evaluated the effects of roller mill configuration on growth performance of nursery and finishing pigs, feed preference, and feed mill throughput. The four experimental treatments included corn ground through a roller mill using two, three, four sets of rolls in a fine-grind configuration, or four sets of rolls in a coarse grind configuration. There was no evidence of differences observed for average daily gain (ADG) or average daily feed intake (ADFI) between roller mill configurations when fed to nursery pigs. However, when given a choice nursery pigs consumed more of the diet containing corn ground through the 2-high roller mill or 4-high coarse configuration compared to corn ground through the 4-high fine configuration. Finally, finishing pigs fed corn ground with the 2-high configuration had greater ADG compared to those fed corn ground using the 3-high configuration. Grinding rate was greatest for the 4-high coarse configuration, while net electricity consumption was lowest for the 2-high configuration and greatest for the 4-high fine configuration. Chapter 2 evaluated the impact of commercial feed additives on the quantification of genetic material and infectivity of swine feed inoculated with porcine epidemic diarrhea virus (PEDV). The combination of essential oils and benzoic acid enhanced degradation of PEDV ribonucleic acid (RNA) in feed but had little impact in spray-dried porcine plasma. In addition, differences in viral stability was observed between feed and spray-dried porcine plasma where PEDV could be detected and remained infectious longer compared to swine feed. Chapter 3 evaluated the impact of flushing feed manufacturing equipment with rice hull flushes following mixing PEDV infected feed. Flushing effectively reduced the quantity of detectible RNA present after mixing a batch of PEDV-positive feed. Furthermore, chemical treatment of rice hulls with formaldehyde or 10% medium chain fatty acid (MCFA) provided additional reduction in RNA detection. Chapters 4 and 5 evaluated the inclusion of added chromium (Cr) in finishing diets. In chapter 4, small differences in ADG and feed efficiency were observed with added Cr. In chapter 5, adding Cr along with Yucca schidigera led to modest changes in performance with the greatest benefit observed with 200 µg/kg Cr and 125 mg/kg Yucca schidigera-based feed grade concentrate. Chapter 6 evaluated the impact of feeding MCFA to nursery pigs and demonstrated improved growth performance, but did not significantly alter fecal microbial composition, and provided residual mitigation activity when inoculated with PEDV following feed storage. Overall, evaluation of feed manufacturing technologies and various feed additives demonstrates potential to have a significant impact on the efficiency of swine production. Additionally, understanding the role that feed and feed transportation contributes to health of swine populations is critical for maintaining a high health and productive global swine industry.
Keywords: Swine; Porcine epidemic diarrhea virus; Medium chain fatty acid; Chromium; Feed processing; Particle size